Analisis Teori Penawaran dalam Ekonomi Manajerial: Suatu Systematic Literature Review - Annisa Hellena Silvi Kuattami; Supriyanto . (Jurnal Ekonomi dan Bisnis Digital, 2026)
This research aims to analyze various theoretical and empirical approaches regarding the theory of supply from a managerial economics perspective thru the Systematic Literature Review (SLR) method with the PRISMA approach to analyze the theory of supply from a managerial economics perspective. Thru the selection of 30 articles from reputable databases, this study identifies that the supply function is significantly influenced by output prices, input costs, technology, the number of producers, and price expectations. The findings indicate that supply elasticity is a crucial indicator for managers in capacity decision-making and pricing. However, there is a research gap because the majority of studies are still partial. The novelty of this research lies in the integrative synthesis between classical theory and modern industrial dynamics, including the manufacturing and digital sectors. The research results provide practical implications for managers, particularly in developing industrial areas such as Bekasi, to make production decisions that are more efficient, adaptive, and sustainable in facing market fluctuations holistically.